OPTIMISATION OF THE SELECTION PROCESS IN FOOTBALL GAME FOR 10-12 YEARS OLD CHILDREN - MONEA, Dan; ORMENISAN, Septimiu; GROSU, Emilia; APOSTU, Paula; NICA BADEA, Delia (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2015)
The essence of the selection is to establish a diagnosis, a prognosis of the future developments in the field of sports performance. As a basic tool in this action are at our command the tests. Regarding sports performance, these issues were discussed in several meetings of the European Federation for Sport and Corporal Activities, having the goals the standardization of the tests in sport. The final conclusions certify the unanimous use of the psychomotor tests, appropriate to the studied group age. It was proposed to establish some batteries of tests and the analysis of the results for planning the age-specific sports training.